EVALUASI PROGRAM PPL DAN KKM TERPADU MAHASISWA IKIP-PGRI PONTIANAK KALIMANTAN BARAT - Kaswari Kaswari (Jurnal Evaluasi Pendidikan, 2016)
The purpose of this study is to obtain actual information about the effectiveness and efficiency of the implementation of integrated PPL-KKM program at IKIP-PGRI Pontianak. This study focused on the evaluation of the implementation including: PPL-KKM conceptual basis of integration, initial preparation activities, PPL-KKM integrated implementation, and results of the implementation of the integrated PPL-KKM. This program evaluation study is conducted by using CIPP (context, input, process, and product) model. Data were collected through documentation, interviews, questionnaire, observation, and analysis with descriptive qualitative method. The data were analyzed to determine success criteria of the implementation and then used as the basis for making decisions. The results of the study suggest that the planning, implementation, and evaluation of integrated PPL-KKM programs has been successful and receive positive response and is proven useful. Therefore, the implementation of the PPL-KKM integrated program may be continued and enhanced.